The Influence the Picture Exchange Communication System Method toward The Communication Ability of Autistic Child - Citra Rizky Ratna Putri; Wiwik Dwi Hastuti; Eka Pramono Adi (Department of Special Education, 2018)
Children with autism have some very complex developmental disorders including communication, social interaction, emotions, and interest in certain behaviors. They need certain tools and methods for developing communication and language skills, especially in speaking skills. One of the methods is the Picture Exchange Communication System method. This research was conducted by using the Single Subject Research method with A-B-A design. Data collection was conducted in 20 sessions. The results of this study indicated that the effect of PECS method towards communication ability of children with autism. This was evidenced by an overlap percentage of 0%. The conclusion showed that PECS method has an effect towards the communication ability of autistic children